Metal fume fever: a case report and review of the literature. Issue 3 (1st May 2002) - Kaye, P; Young, H; O'Sullivan, I
Abstract : Metal fume fever is an acutely noxious inhalation syndrome secondary to metal oxide fumes. Despite preventative strategies sporadic cases are likely to continue to present to emergency departments.